Investigation on ways to improve capacity utilization: case of Sable. - Chiseva, Wellington (Midlands State University, 2017)
The study was aimed at addressing the problem of persistent capacity utilization problems faced by Sable Chemical Industries limited. The major objectives of the research study were the determination of the basis of calculating capacity, capacity-utilization, under-capacity utilisation, major causes of under-capacity utilisation, and effects of under-capacity utilisation to both the entity and the economy in its entirety and to prescribe the possible solutions to reverse the endangering macro-economic disease. The research was a qualitative study using the descriptive research design. Interviews and questionnaires were used as research instruments and were administered at Sable Chemicals Industries Limited’s Head office in Kwekwe to the selected respondents (sample of 26 and 24 participated in the study) chosen on the merits of a purposive sampling technique. The study revealed that electricity (i.e. cost of power and availability), financing and liquidity problems, indigenization policy, plant breakdowns and over-estimation of capacity have contributed to low rates of production. Further to that, the research went on to prescribe recommendations which include securing stable and cost effective, revising the production capacity, review of the indigenization policy, considering the adoption of local powerful currencies and considering allowing flexible-labour market laws among other factors.